Prediction of the Satisfaction With the Student Life, Based on Teaching Competence and Satisfaction With the School - Baños, Raúl; Baena-Extremera, Antonio; Ortiz-Camacho, María del Mar (Frontiers in Psychology, 2019)
The aim of this article was to assess how students evaluate the professional personality competence of physical education teachers in high school and its relation to student satisfaction and student satisfaction with life itself. In line with these aims, this study was completed as a cross-sectional study, which was carried out in a group of 890 physical education students. Of the study group, 50.3% were female and 49.7% were male. The average age was 15.49 years for females (SD 1.79) and 15.00 years for males (SD 2.00). We used a questionnaire featuring the Physical Education Teacher Competence, Intrinsic Satisfaction Classroom Scale, and Satisfaction with Life Scale. The results are presented as descriptive statistics, correlations, and a structural equation modeling analysis showing students’ perceived competence, predicted self-determined satisfaction, which in turn corresponds to life satisfaction.